Karakter Visual Candi Bentar Pura Puru Sada di Badung, Bali - I Putu Sathya Dharma; Gusti Ayu Made Suartika (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2022)
Candi bentar is a gate or the main door to enter a specific area, such as temple and palace in Bali. However, in the current situation, it can be found in many entries points to various premises, including a border between areas, a house, and public facilities. Puru Sada Temple, one of Kahyangan Jagat Temples located in Badung Regency of Bali Province, has a candi bentar, which at first glance similar to that of the Wringin Lawang Temple - a legacy of the Majapahit Kingdom of East Java. In terms of scale, however, the size of the Puru Sada Temple’s candi bentar is smaller. The purpose of this study is to discuss the visual characters of candi bentar in places that functioned for worship by taking Puru Sada Temple as its case study. The study used a descriptive qualitative approach. Its analysis is supported by relevant views offered by both Yudoseputro (2008) and Ching (1991). This study finds that intimacy has been a dominant visual character supported by the existence of sacred ornaments that are considered as guarding figures. Keywords: visual character; candi bentar; gate; Puru Sada Temple Abstrak Candi bentar adalah gerbang atau pintu utama dalam memasuki area khusus seperti pura maupun puri di Bali. Namun saat ini candi bentar dapat ditemukan di berbagai tempat seperti perbatasan daerah, rumah tinggal, dan fasilitas umum. Pura Puru Sada termasuk dalam Pura Kahyangan Jagat berlokasi di Badung memiliki candi bentar yang sekilas mirip dengan Gapura Wringin Lawang peninggalan Kerajaan Majapahit di Jawa Timur. Namun ukuran candi bentar Pura Puru Sada lebih kecil. Tujuan penelitian ini adalah membahas karakter visual candi bentar di tempat suci dengan mengambil Pura Puru Sada sebagai studi kasus. Penelitian ini menggunakan pedekatan kualitatif deskriptif. Dianalisa dengan teori relevan yang ditawarkan oleh Yudoseputro (2008) dan Ching (1991). Studi ini menemukan jika intimasi merupakan karakter visual dominan yang didukung dengan adanya ornamen sakral sebagai sosok penjaga. Kata kunci: karakter visual; candi bentar; gapura; Pura Puru Sada